William S. Searle scrapbook and certificate - Searle, William S., 1833-
Scrapbook containing correspondence, clippings, pamphlets, photographs, and other papers concerning Searle's career as a homeopathic physician in Brooklyn, N.Y., and his service as Henry Ward Beecher's physician. Includes a certificate from the Brooklyn Medical Club. Correspondents include Beecher, Melvil Dewey, Ainsworth Rand Spofford, Harriet Beecher Stowe, and William H. Vanderbilt.
Physician.
Collection material in English.
Keywords: Beecher, Henry Ward, -- 1813-1887.; Beecher, Henry Ward, -- 1813-1887 -- Correspondence; Dewey, Melvil, -- 1851-1931 -- Correspondence; Spofford, Ainsworth Rand, -- 1825-1908 -- Correspondence; Stowe, Harriet Beecher, -- 1811-1896 -- Correspondence; Vanderbilt, William H. -- 1821-1885 -- Correspondence; Brooklyn Medical Club; Homeopathy; Medicine -- Societies, etc; Medicine -- Practice -- New York (State) -- New York; Brooklyn (New York, N.Y.); Physicians